THE COMMODIFICATION OF ROMANCE THRILLER IN NETFLIX’S YOU SERIES - Sinaga, Leny Roslinda (Rubikon : Journal of Transnational American Studies, 2025)
This study aims to determine how the You series uses the male gaze to commodify romance and thriller elements and manipulate aspects of the genre to draw viewers. Additionally, the analysis of the You series reveals that it questions patriarchal beliefs and gender representation in the media. In reviewing this research, qualitative analysis methods were used, and Laura Mulvey's Male Gaze theory was applied to analyze the data after examining primary and secondary data and finding supporting theories for the data. This research also uses a Transnational perspective to understand how Netflix produces, distributes, and consumes this genre in various countries and cultures. The result of this research concluded that the You series criticized the dynamics in heterosexual relationships, especially the concept that men should protect women in a way that often leads to control and violence. The You series encourages the audience to reconsider protection in relationships, exposing how these seemingly ideals can be weaponized and distorted into control, obsession, and violence.